Natality Detail File, 2004 (United States) ([Verlag nicht ermittelbar], 2008)
This collection provides information on live births in the United States during calendar year 2004. The natality data in these files are a component of the vital statistics collection effort maintained by the federal government. Birth data are limited to births occurring in the United States to United States residents and nonresidents. Births occurring to United States citizens outside of the United States are not included in this data collection. Part 1 contains data on births occurring within the United States, while Part 2 contains data on births occurring in the United States territories of Puerto Rico, the Virgin Islands, Guam, American Samoa, and the Commonwealth of the Northern Mariana Islands. Geographic variables include the state and county in which the birth occurred, as well as the population size of the county. Other variables describe the place of delivery, who was in attendance, and medical and health data such as the method of delivery, the number of the prenatal visits, tobacco and alcohol use during pregnancy, pregnancy history, medical risk factors, and infant health characteristics. Birth and fertility rates and other statistics related to this study can be found in the National Vital Statistics Report in the codebook documentation. Demographic variables include the child's sex and month and year of birth, the parent's age, race, and ethnicity, as well as the mother's marital status, education level, place of residence, and place of birth.